2022
DOI: 10.1002/jcla.24685
|View full text |Cite
|
Sign up to set email alerts
|

Serum VCAM‐1 and ICAM‐1 measurement assists for MACE risk estimation in ST‐segment elevation myocardial infarction patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…ICAM-1 plays a fundamental role in neutrophil crossing of the endothelial cell layer [88]. Yu et al [89] have found that stress [90]. Similarly, we found that both RELA and ICAM-1 were stably upregulated in the disgroup.…”
Section: Discussionsupporting
confidence: 77%
“…ICAM-1 plays a fundamental role in neutrophil crossing of the endothelial cell layer [88]. Yu et al [89] have found that stress [90]. Similarly, we found that both RELA and ICAM-1 were stably upregulated in the disgroup.…”
Section: Discussionsupporting
confidence: 77%
“…The models sharing identical predictor variables and stemming from the same study population, yet predicting MACE at varying time intervals, were categorized as one model. A total of 12 studies addressed prognostic models for patients with ST-segment elevation myocardial infarction (STEMI) ( 20 , 26 – 29 , 32 34 , 36 39 ). Six studies were centered on patients with myocardial infarction (MI) ( 11 , 12 , 21 , 22 , 24 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 91.3% of the studies ( n = 21) were constructed using Chinese populations, while one study ( 31 ) was based on England individuals, and another study ( 37 ) was based on Spain individuals. The models developed in the eight studies ( 21 , 24 , 25 , 30 , 33 , 37 , 39 ) did not undergo either internal or external validation. Three studies performed external validation by enrolling patients at different times ( 11 , 31 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TNF-α promotes the interconnection between the endothelium and circulating leukocytes by the upregulation of adhesion molecules such as vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1) ( 10 ). High levels of VCAM-1 and ICAM-1 have been described as an independent risk of major adverse cardiac events ( 18 ). The expression of ICAM-1 and VCAM-1 is associated with intestinal disease activity, demonstrated by the reduction of their serum concentration after treatment ( 10 , 19 ).…”
Section: Pathological Mechanisms Shared By Ibd and Atherosclerotic Ca...mentioning
confidence: 99%